Towards a cognitive forensic stylistics: An intercoder reliability test for replicable feature finding in the Operation Heron corpus - Voice, Matthew; Harrison, Chloe; Grant, Tim; Giovanelli, Marcello (Language and literature (Harlow, England), 2025)
This paper reports an initial application of contemporary cognitive stylistics to forensic linguistic contexts. In both areas, a need has been identified for robust analyses. An intercoder reliability study was developed using data from a historic authorship analysis case involving single-authored hate mail. Exploring the applicability of Cognitive Grammar’s notion of construal as a reliable framework for describing salient features of the author’s style, this test examined the accuracy and consistency of descriptions of schematicity and specificity within the corpus, as applied by independent coders. Iterative coding and testing demonstrated that reliability was achievable, but depended upon a protocol developed through considerable definitional work, refining the concepts of specificity and elaboration as taken from Cognitive Grammar. Our findings support the idea that the identification of stylistic features can be rigorous, retrievable, and replicable, but also that a fuller system of coding will require a substantial research programme. Such an approach, bringing together contemporary stylistics and forensic authorship analysis, would be a productive collaboration between both disciplines and a valuable research method for verifiability in stylistics more generally. Content: Readers are advised that the letters analysed for this study contain offensive language, and that short quotes within this paper include racist and hateful language directed at particular groups.